Independensi Auditor, Integritas Dan Pengalaman Kerja Terhadap Kualitas Audit - Inge Angelina; Syaiful Syaiful (Journal of Culture Accounting and Auditing, 2022)
This study aims to determine the effect of independence, integrity, and work experience on audit quality. In this research, the researcher examines the audit quality at the Public Accounting Firm (KAP) in the city of Surabaya by using the independent variables, namely independence, integrity and work experience.The population in this study are several auditors who work at KAP in the city of Surabaya. Sampling was carried out using purposive sampling method, and the number of samples was 47 respondents from 13 KAP in Surabaya. The primary data collection method used is a questionnaire method with several criteria. Data collection is done by sending questionnaires via broadcast messages and email in the form of google from. The data analysis technique used in this research is multiple regression analysis technique.The results of hypothesis testing in this study indicate that independence, integrity, and work experience have a significant and significant effect on audit quality. The researcher suggests future research to add more variables and to expand the population..